Children's exhaustive readings of questions. (2nd October 2017) - Cremers, Alexandre; Tieu, Lyn; Chemla, Emmanuel
ABSTRACT: Questions, just like plain declarative sentences, can give rise to multiple interpretations. As discussed by Spector & Egré (2015), among others, questions embedded under know are ambiguous between weakly exhaustive (WE), intermediate exhaustive (IE), and strongly exhaustive (SE) interpretations (for experimental evidence of this ambiguity, see Cremers & Chemla 2016). These three interpretations are related in terms of strength. The SE reading entails both the IE and WE readings, and the IE reading entails the WE reading. Certain proposals derive the stronger readings from weaker ones through the same process of enrichment that underlies scalar implicatures, in particular through comparison with alternatives (Klinedinst & Rothschild 2011). Given previous developmental studies of scalar implicatures that suggest children typically perform this enrichment less often than adults do (Noveck 2001; Chierchia et al. 2001; Papafragou & Musolino 2003, among many others), such proposals lead us to expect that children may initially prefer weak readings of embedded questions. The present study revealed that 5-year-olds were sensitive to the multiple readings of questions embedded under savoir 'know.' Compared to adults, however, children were more tolerant of weak readings. These findings relate scalar implicatures and exhaustive readings of embedded questions from a developmental perspective and are consistent with a close connection between the two: in both cases, children are sensitive to the various possible interpretations but favor the weaker one more than adults do.